Pelvic Floor Dysfunction and Pelvic Surgery in the Elderly An Integrated Approach - Gordon, David A.; Katlic, Mark R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2017)
This text provides a comprehensive, state of the art review of this field and will serve as a resource for urologists, colorectal surgeons, geriatricians, and gynecologists as well as researchers interested in neuromuscular phenomena in the pelvis. The book also reviews new data regarding risk factors for pelvic floor muscle dysfunction and profiles new minimally invasive surgical strategies for well known pelvic disease processes. Each chapter is chock full of data from landmark trials which have been published over the past few years and placed in context with respect to current management techniques for pelvic floor disorders. Written by experts in their field, Pelvic Floor Dysfunction and Pelvic Surgery in the Elderly: An Integrated Approachprovides a concise yet comprehensive summary to help guide patient management.
Anatomy, Neuroanatomy and Biomechanics of the Pelvis -- Pelvic Floor Physiology: From Posterior Compartment to Perineal Body to Anterior Compartment -- Cellular and Molecular Aging -- Principles of Geriatric Surgery -- Nutritional Considerations in Pelvic Medicine & Surgery -- Microbiology of Virulence: Urinary Tract Infection versus Colonization -- Chronic Catheter Associated Complications and Catheter-Associated Urinary Tract Infection -- Physical Therapy Evaluation and Treatment of Pelvic Floor Dysfunction Including Hypertonic Pelvic Floor Dysfunction -- Multichannel Urodynamic Testing -- Anorectal Manometry -- Functional Anorectal Imaging: Radiologic Considerations and Clinical Implications -- Colonoscopy in Elderly Patients -- Treatment Options For Stress Urinary Incontinence -- The Neurogenic Bladder and Hypertonic Pelvic Floor Muscle Dysfunction -- Biology of Pain and Pathophysiology of Pelvic Pain Syndrome -- Interstitial Cystitis: The Painful Bladder Syndrome -- Overactive Bladder (OAB) in The Elderly with Contemporary Notions on Treatment including Sacral Nerve Stimulation (SNS) -- Sacral Neuromodulation in Interstitial Cystitis -- Therapeutic neural blockade -- Pelvic Organ Prolapse in the Older Woman -- Robotic Pelvic Surgery: Historical Perspective, Single Site Robotic Surgery & Robotic Sacral Colpopexy -- Genito-Urinary Fistulae: Vesicovaginal, Ureterovaginal and other Urinary Fistula -- Rectal Prolapse in the Elderly -- Fecal Incontinence -- Colorectal Interventions: Chronic Constipation -- Fecal Diversion and Ostomies -- Pelvic Hernias -- Colorectal Interventions: Rectovaginal Fistulas -- Colorectal Interventions: Benign Anorectal Disease.
Keywords: Medicine; Gynecology; Geriatrics; Rectum -- Surgery; Urology; Medicine & Public Health; Urology; Colorectal Surgery; Geriatrics/Gerontology.; Gynecology